Handbook of muscle foods analysis - Toldra, Fidel (CRC Press, 2009)
Discusses the importance of the essential amino acids, vitamins, and minerals that are found in muscle foods. This book presents a comprehensive overview and description of the analytical techniques and application methodologies for this food group that comprises much of the Western diet.